Evaluation of the Antibacterial Activity of the Jackfruit Parasite Leaf Plant Extract (Macrosolencochinchinensis (Lour.) van Tiegh) with Vitro and In Silico approach - Rahmiwati Hilma; Suma Rahmani Harahap; Jufrizal Syahri (The University of Mataram, 2022)
In traditional Melayu Riau medicine, the jackfruit parasite plant, also known as Macrosolen cochinchinensis (Lour.) van Tiegh, has been utilized as a remedy for coughs, a treatment for cancer, a diuretic, and to speed up the recovery process after giving birth. Through in vitro and in silico testing, this investigation aims to learn more about the bioactive components and antibacterial activity of n-hexane, ethyl acetate, and ethanol obtained from the extracts of the jackfruit parasite plant (Macrosolen cochinchinensis (Lour.) van Tiegh. The disc diffusion method was used for the in vitro testing, and the molecular docking method was used for the in silico testing. Both were conducted against Staphylococcus aureus ATCC 12600 and Escherichia coli ATCC 25922. Each sample extract was prepared in three different concentrations (10%, 30%, and 50%), while chloramphenicol was used as the positive control. Inhibition zones of the extract against E. coli bacteria were found to be as follows: 6 mm, 8.4 mm, and 10.6 mm for the n-hexane extract; 8.2 mm, 10.7 mm, and 15.6 mm for the ethyl acetate extract; and 6 mm, 7.1 mm, and 14.1 mm for the methanol extract. The results of the test to determine the extract's antibacterial activity were as follows: The following is a list of the zones of inhibition that the extract has against S. aureus bacteria: 6 mm, 7.5 mm, and 13.7 mm in diameter for the extract of n-hexane; 12.8 mm, 14.2 mm, and 19.2 mm in diameter for the extract of ethyl acetate. Test results of 7.2 mm, 9.3 mm, and 15.3 mm were obtained for the methanol extract. In accordance with the findings of the study, the ethyl acetate extract of jackfruit parasite leaves exhibited the highest level of antibacterial activity, as measured by an inhibition zone diameter of 19.2 mm, when tested on S. aureus bacteria. In the meantime, the results of molecular docking of punicalin and rutin, which have been reported to have activity against proteins 6GOS.pdb and 1OJZ.pdb, have potential as antibacterials because they form 5 and 9 hydrogen bonds with important amino acids of the target protein, with cDOCKER values of -57.9239 and -88.3993, respectively. It suggests that punicalin and rutin can inhibit the growth of bacteria.